Comparison between Law No. 1 of 1974 and Islamic Law Regarding the Customary Marriage System of Nikka Ada' in Mamuju Society - Muh Ishar; Hannani; Saidah; Agus Muchsin; Suarning (Universitas Muhammadiyah Palu, 2024)
he main issues addressed in this research are: 1) The meaning and process of Nikka Ada' implementation in Mamuju, 2) Islamic law's perspective on the practice of Nikka Ada' in Mamuju, and 3) The view of National Law No. 1 of 1974 on marriage regarding the practice of Nikka Ada' in Mamuju. This study adopts a qualitative approach with descriptive research, utilizing oral questioning. The theoretical frameworks employed include comparative theory, customary wisdom, and maslahah mursalah. The findings of this research conclude that: 1) The process of divorce marriage in Kalukku sub-district is similar to conventional marriage practices, with the groom providing a dowry, witnesses, a guardian, and other customary requirements. The local customs dictate that the marriage is considered complete upon dissolution (divorce). Pregnant women will divorce when the child is born. 2) The phenomenon of divorce marriage in Kalukku sub-district, considering its purposes, brings more benefits than harm. Therefore, based on Quranic verses, Hadiths, and Islamic legal principles, the practice of divorce marriage in Kalukku sub-district is permissible, provided it is undertaken out of necessity to bring about benefits. 3) Nikka Ada' marriages in Kalukku sub-district contradict the prevailing laws as they are not conducted through a court hearing. Divorce occurs solely based on the agreement of both parties, their respective families, and community and customary leaders.